The features of cinema hall acoustics upon installation of the dolby sound recording system/Kino teatro akustikos ypatumai, įrengus “dolby” įgarsinimo sistemą - Stauskis, Vytautas (Journal of Civil Engineering and Management, 1999)
Investigations conducted in a cinema hall have shown that the character of the sound field decay in all rows of the main floor is uniform. The character of the sound field decay in the balcony is similar to that on the main floor. The maximal decay energy in the balcony is lower by about 2 dB compared to that on the main floor. After the reconstruction of the hall, the energy decay of a similar character was found both on the main floor and in the balcony. The decay of energy is much faster because the sound absorption of the entire hall has increased. The maximal energy values, however, are higher in the balcony and under it compared to the main floor. After the reconstruction the overall hall absorption has increased by about 200–300 m2 both on the main floor and in the balcony. Consequently, the reconstruction should have resulted in the decrease of the maximal energy in both areas. Actually, the maximal energy value is higher in the balcony. At the frequency 63 Hz, the maximal energy value in the balcony after the reconstruction, ie after the increase in the overall absorption, is by 10 dB higher than that before reconstruction when the absorption was smaller. One would expect a reverse. A similar effect is observed in the rows under the balcony. At 1000 Hz and 2000 Hz the energy increase is 4–5 dB and it starts after 50 ms. At 4000 Hz a maximal energy increase of 7–8 dB is reached after 100 ms. Before the reconstruction the early reverberation time T10 markedly exceeded the permissible upper limit in all rows of the hall, and particularly at the end of the hall and in the balcony at the frequency from 63 to 500 Hz. As the sound field decay was approximated by larger level intervals, eg from 0 to −30 dB, still larger reverberation time values were obtained. After the reconstruction the early reverberation time in all rows of the main hall and the balcony does not exceed the permissible upper limit. It is only in the frequency range of 250–1000 Hz that the reverberation time values are below the lower limit. In this case, the listener’s subjective perception will be of a weaker sound, which is strongly preferable, since the sound is too strong in Lithuanian cinema halls where the Dolby sound-recording system has been installed. Article in Lithuanian. First Published Online: 26 Jul 2012